WEB based process control laboratory implementation - Chacón Montiel, Edgar; Camacho, Oscar; Cárdenas, Oscar (Rev. Téc. Fac. Ing. Univ. Zulia, 1970)
This paper describes the development and implementation of a “Web bas d Process Control Laboratory”. which will be part of the curricula of the Electrical Engineering School at Universidad de Los Andes, Mérida, Venezuela. The Laboratory uses instructional techniques throughout Web collaborative learning.